Scaffolds for Pelvic Floor Prolapse: Logical Pathways - Julio Bissoli; Homero Bruschini (International Journal of Biomaterials)
Pelvic organ prolapse (POP) has borrowed principles of treatment from hernia repair and in the last two decades we saw reinforcement materials to treat POP with good outcomes in terms of anatomy but with alarming complication rates. Polypropylene meshes to specifically treat POP have been withdrawn from market by manufactures and a blank space was left to be filled with new materials. Macroporous monofilament meshes are ideal candidates and electrospinning emerged as a reliable method capable of delivering production reproducibility and customization. In this review, we point out some pathways that seem logical to be followed but have been only researched in last couple of years.